Peningkatan hasil belajar siswa kelas VI pada pembelajaran PKn melalui tipe pembelajaran Pair Checks di SDN 45 Jambak Pesisir Selatan - Arnida Arnida (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
This study aims 1) To describe the PTK improvement of cognitive learning outcomes (knowledge) of students of class VI on learning civics through Type Pair Checks at SDN 45 Jambak Pesisir Selatan. 2) To describe the PTK to increase the affective learning outcomes (responsibility) of the sixth-grade students on the learning of Civics through the type of learning Pair Checks at SDN 45 Jambak Pesisir Selatan. This study was conducted in two cycles, each cycle consisting of two meetings and one final test cycle. The subjects of this study are students of class VI, which amounted to 12 people. Based on the results of this study it can be concluded that the use of Pair Checks Learning Type can improve the learning outcomes of Civics in grade VI SDN 45 Jambak Pesisir Selatan.